Binding Specificity and Oligomerization of TSWV N Protein in the Western Flower Thrips, Frankliniella occidentalis - Falguni Khan; Eticha Abdisa; Niayesh Shahmohammadi; Yonggyun Kim (Viruses, 2025)
Tomato spotted wilt virus (TSWV) is a highly destructive plant pathogen and transmitted by several thrips including the western flower thrips, Frankliniella occidentalis. A structural N protein encoded in the viral genome represents the nucleocapsid protein by binding to the viral RNA genome. However, it remains unknown how the RNA-binding protein specifically interacts with the viral RNA from host RNAs in the target cells. To study the molecular basis of N function, we produced the protein in Escherichia coli and the resulting purified recombinant protein was used to investigate the protein–RNA interactions. The recombinant N protein migrated on agarose gel to the anode in the electric field due to its high basic isoelectric point. This electrostatic property led N protein to bind to DNA as well as RNA. It also bound to both single-stranded (ssRNA) and double-stranded RNA (dsRNA). However, when the total RNA was extracted from plant tissues collected from TSWV-infected host, the RNA extract using the recombinant N protein was much richer in the TSWV genome compared to that without the protein. To investigate the specificity of N protein to ssRNA, the three-dimensional structure was predicted using the AlphaFold program and showed its trimeric oligomerization with the binding pocket for ssRNA. This was supported by the differential susceptibility of N protein with ssRNA and dsRNA against RNase attack. Furthermore, a thermal shift assay to analyze the RNA and protein interaction showed that ssRNA strongly interacted with N protein compared to dsRNA. In addition, the N gene was expressed along with the multiplication of the viral RNA genome segments from the segment-specific fluorescence in situ hybridization analysis in different tissues during different developmental stages of the virus-infected F. occidentalis. These results suggest that the functional trimeric N proteins bind to the viral RNA to form a basic nucleocapsid structure at a specific virus-replicating compartment within the host cells.